Providing the Judiciary with Qualified Personnel and the Role of Human Rights Education in this Process (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Within the framework of this article, the training of judges, which is one of the subjects of judicial authority in Uzbekistan, that is, the system of judicial education, its legal basis, forms of education, educational process, and priority tasks in this regard are considered. The organization of human rights education for candidates for the post of judge, its purpose, legal basis and implementation mechanisms are also analyzed.